Auxiliary specialization opportunities in landscape architecture: nature of profession, current view, allied relationships, skills & knowledge, and future directions - Weber, Gabriela (Kansas State University, 2015)
Landscape architecture’s scope of knowledge and professional practice is continuously broadening. Formalized certification and certification standards do not exist to date; as a result, limiting the depth of knowledge in landscape architects. Beyond competency in core skills like natural systems, site planning and design, and visualization graphics, the general knowledge base of most landscape architects spans a variety of disciplines. This ability to “see the bigger picture” offers certain strengths when “placemaking”, interacting with allied professionals, and leading project teams; yet there are limited opportunities for landscape architects to formally develop a depth of expertise. An extensive literature search identified forty-one knowledge domains that exist in landscape architecture. This report identifies fourteen domains that landscape architects need in current and future work supported with identified core skills and knowledge in the profession. This report seeks to update the Council of Landscape Architecture Registration Board’s (CLARB) identification of knowledge domains by layering skills and knowledge found in sixty current job postings, literature search, and structured interviews. In addition, this report identifies future trends in the profession and marketplace and future dilemmas landscape architects must address in the next twenty years. Content analysis of certification programs offered to landscape architecture students at accredited schools was conducted. A certification precedent study was conducted to understand the range of certification standards that exist in order to propose a standardized certification program. Thirteen themes are identified in the structured interviews that are incorporated into themes of this report. Overall, professionals feel that landscape architecture’s strength as a generalist profession makes the profession unique from its allied professions. However, some professionals acknowledge that as a landscape architect progresses in his or her career, they tend toward areas of specialization. This report suggests that certifications be offered to graduate students and professionals, explains specialization in the profession, and identifies areas landscape architects need to increase their skills and knowledge in, to stay relevant.
Keywords: Landscape architecture; Certification; Knowledge domain; Specialization; Skills and knowledge; Future dilemmas; Landscape Architecture (0390)